The Correlation between the Use of WhatsApp in Learning Arabic and Student's Motivation and Achievement During the Covid-19 Pandemic / العلاقة بين استخدام واتسـاب في تعليم اللغة العربية في دافعية الطلاب وإنجازهم في جائحة كوفيد-19 - Latifah, Nuri Nurul (UIN Raden Mas Said Surakarta, 2021)
This study aims to determine the correlation of the use of WhatsApp as social media in learning Arabic to students' motivation and achievement during the Covid-19 Pandemic at Al-Mu'min Paseh Integrated High School Kab. Bandung for the academic year 2020/2021. The method used in this research is the descriptive correlational method, with a research sample of 30 respondents from class X and XI at